CellDyM: A room temperature operating cryogenic cell for the dynamic monitoring of snow metamorphism by time‐lapse X‐ray microtomography. Issue 10 (18th May 2015) - Calonne, N.; Flin, F.; Lesaffre, B.; Dufour, A.; Roulle, J.; Puglièse, P.; Philip, A.; Lahoucine, F.; Geindreau, C.; Panel, J.‐M.; du Roscoat, S. Rolland; Charrier, P.
Abstract Monitoring the time evolution of snow microstructure in 3‐D is crucial for a better understanding of snow metamorphism. We, therefore, designed a cryogenic cell that precisely controls the experimental conditions of a sample while it is scanned by X‐ray tomography. Based on a thermoelectrical regulation and a vacuum insulation, the cell operates at room temperature. It is, thus, adaptable to diverse scanners, offering advantages in terms of imaging techniques, resolution, and speed. Three‐dimensional time‐lapse series were obtained under equitemperature and temperature gradient conditions at a 7.8 μm precision. The typical features of each metamorphism and the anisotropic faceting behavior between the basal and prismatic planes, known to occur close to −2°C, were observed in less than 30 h. These results are consistent with the temperature fields expected from heat conduction simulations through the cell. They confirm the cell's accuracy and the interest of relatively short periods to study snow metamorphism.